Results of a Randomized, Multi-Center Safety Trial of Perflutren Lipid Microspheres: TUCSON - Vinall, Maria (MD Conference Express, 2009)
Microspheres that are combined with systemic tPA and rational transcranial Doppler show promise as a recanalization tool in patients with acute ischemic stroke if administered within 3 hours of stroke onset. This article discusses results from the Transcranial Ultrasound in Clinical SONolyis [TUCSON; NCT00504842] trial, identifying 1.4 mL of MRX-801 perflutren lipid microspheres as a safe dose that produces higher rates of recanalization (67% vs 33%; p=0.22) compared with controls.